Contact Transfer Printing: Contact Transfer Printing of Side Edge Prefunctionalized Nanoplasmonic Arrays for Flexible microRNA Biosensor (Adv. Sci. 9/2015). Issue 9 (September 2015) - Lee, Jihye; Park, Jiyun; Lee, Jun‐Young; Yeo, Jong‐Souk
<x xml:space="preserve">Abstract</x> A scalable contact‐transfer printing of an ultrasensitive, flexible nanoplasmonic biosensing platform for miRNA‐21 is presented by J.‐S. Yeo and co‐workers in article number 1500121. The greatly increased sensitivity and suppressed noise result from selective pre‐functionalization on the sidewalls of the nanostructures to enhance the electric field. Arrays of the nanostructures form hetero assemblies, which are contact‐transfer printed onto flexible substrates.